Organization of the human HLA-class-II region. - Hanson, I; Ragoussis, I; Trowsdale, J (1991)
A detailed map of the class-II region of the human MHC has been established by pulsed-field-gel-electrophoresis (PFGE) mapping and cloning in yeast-artificial-chromosome (YAC) vectors. The map revealed CpG islands, which are frequently associated with genes, in the gaps between the known HLA-class-II genes. Using cosmid walking and chromosome jumping, we have cloned 3 of these islands and have identified 5 novel genes, named RINGI-5. This brief report summarizes our present knowledge of these genes.